Al-Qanun Al-Kulliy: A philosophy in understanding faith in Islam - Akila, Mamat; Mohammed Muneer'deen, Olodo Al-Shafi'i; Aminudin, Basir@Ahmad; Shamsuddin, Yabi (2017)
This article discusses the concept of al-Qanun al-Kulliy as a philosophy in under-standing the meaning of the verses of the Qur’an and Hadith of the Prophet (S.A.W), both of which are needed in understanding faith-related issues. The concept here is that sense of purpose, considered priority in outward evidences of Islamic law, which has drawn criticism from Islamic scholars who cling to the methods of the Salaf al-Salih. To understand the concept of al-Qanun al-Kulliy, this paper relies on the analysis of some related sources, the study of which has shown that al-Qanun al-Kulliy is a philosophy in understanding matters of faith that was adopted by some theologians (Ahl al-Kalam). The paper also shows that Ibn Taimiyyah and his student, Ibn al-Qayyim, are among Muslim scholars who maintain firm criticism of al-Qanun al-Kulliy on the premise that it denies many faith-related issues stipulated by the texts of personality (qat’iy). The paper adopts a qualitative approach, being mainly a library-based research study. The aim of the paper is, therefore, to maintain al-Qanun al-Kulliy as a means to understand-ing faith in Islam if properly employed.